The Palaeo-Kambaniru river mouth, Sumba, East Nusa Tenggara, Indonesia: A record of strongly seasonal catastrophic flow in a monsoon-controlled deltaic complex - Zonneveld, John-Paul; Zaim, Yahdi; Rizal, Yan; Aswan, Aswan; Fortuin, Anne; Larick, Roy; Ciochon, Russell L. (Berita Sedimentologi, 2021)
The Kambaniru River valley near the city of Waingapu preserves a thick succession of coarse-grained fluvial-deltaic sediment deposited during the Late Pleistocene. This succession incises through a thick uplifted coral reef terrace succession and records intervals of highly episodic flow events during the last glacial interval. The occurrence of intraclastic, coarse sand/gravel matrix olistostromes in several areas attests to the occasionally catastrophic nature of flow in the ancestral Kambaniru River. Small to moderate-sized coral-rich reefs and laterally restricted reef terraces occur on delta-front conglomerate successions at multiple horizons through the study interval. These reefs record both intervals of low flow as well as periodic river-mouth avulsion episodes. Comparison of radiometric dates obtained from pelecypod and coral material from both deltaic successions and laterally adjacent coral reef terrace intervals indicates that uplift/subsidence history of the terraces differs from that of the valley and that correlation between the two should be taken with care.